Analisis Aliran Daya dan Stabilitas Sistem Tenaga Listrik Sistem Multi Mesin dengan ETAP - Arief Budi Laksono; Zainal Abidin (Universitas Islam Lamongan, 2020)
Study of the stability of the power system as an important and complex problem in the operation of a power system that is safe from the power system when there are small or large disruptions in the connected power system. This discussion studies load flow and stability analysis while a multi-machine power system with ETAP software.Single diagram system multi-engine system 9-bus system configured in ETAP. For each multi-machine power system power flow and power flow analysis have been provided a complete tool in ETAP.The results of the load flow data are presented for each case. For the transient stability analysis, the system is simulated with three phase disturbance to earth and single phase interference in ETAP. The combination of AVR, Governor, and PSS maintains synchronization during all types of errors. Variations in rotor angle, bus voltage, and engine speed were studied in each case study. Simulation results are shown through graphical analysis. In the ETAP simulation study explains that the application of PSS can substantially improve the transient stability of the power system.